EFEK ROKOK TERHADAP KADAR FOLLICLE STIMULATING HORMONE (FSH) PADA PRIA - Hendri Devita; Vitri Yuli Afni Amran (Indonesia Jurnal Kebidanan, 2019)
Smoking gives  negative impact on the reproductive health of men and women. Various hormones including sex steroid hormones may change, due to the effects of nicotine such as  hypothalamus  shaft - pituitary - gonads and sex steroid hormone metabolism. Nicotine can affect the central nervous system works,  with the resulth  that Gonadotropin Releasing Hormone (GnRH) in the hypothalamus stimulates the anterior pituitary to produce FSH  and to  decrease LH. Decreased FSH  causes stimulation  in Sertoli cells to produce  decreased androgens biding protein (ABP) will also. The purpose of this study was to determine differences in the levels of FSH, LH and testosterone in heavy smokers and smokers.This study was  a cross sectional analytic approach. The population were  heavy smokers and  non smokers at  Baiturrahmah University . Consecutive sampling sampling conducted from the date of December 4, 2014 until January 13, 2015 with the  samples of 50 people. FSH, LH and testosterone were checked at the Laboratory of Biochemistry, University of Andalas. Data analysis was performed by an independent t test. The results showed levels of  FSH in heavy smokers and non smokers  were 3.857 ± 1.493 mIU / ml and 4.977 ± 2.083 mIU / ml with  p value = 0.034.From these results it can be concluded that there were  significant differences in  FSH mean levels in heavy smokers with  the non-smokers